Razvoj in učinki turizma v Rogaški Slatini - Horvat, Uroš (Geografija Slovenije, 2000)
The first part of the book describes the developmental stages of the health resort and the main characteristics of tourist turnover in Rogaška Slatina. The emphasis is on its dependence on tourist demand and supply as well as on changing economic, social and political circumstances. The author points to the gradual loss of Rogaška Slatina's leading role among Slovene health resorts. The second section deals with the demographic, economic and spatial development of the settlement. Since Rogaška Slatina is a multi-functional tourist resort, the emphasis is on the impact of the health resort and tourist provisions as well as industry on the development and structure of work posts, the dynamics of population growth and the economic structure of the population and households. The attitudes of the local population toward health resort-related activities and tourism and the significance of tourist infrastructure for their quality of life are also analyzed.